The Moderating Role of Customer Green Interest in the Relationship between Legal Framework and Green Supply Chain Management of Restaurants in Tanzania - Wabanhu, Emmanuel; Namwata, Baltazar; Panga, Faustine (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study examines the relationship between legal framework (LF) and green supply chain management (GSCM). The study further examines the moderating role of customer green interest (CGT) in the relationship between LF and GSCM. Methodology: The study was conducted in Tanzania, specifically in the Arusha region. A cross-sectional survey was used to collect quantitative data from 386 members of restaurant management teams involved in supply chain operations of restaurants. This sample size was determined using Cochran`s formula since the population of member of restaurant management teams (managers and supervisors) involved in supply chain operations were unknown. Data were collected from respondents through a structural questionnaire. Further, data were analysed using partial least square-structural equation modelling (PLS-SEM). Findings: Findings reveal that LF positively and significantly influence GSCM of restaurants. Moreover, CGI was found to have no moderating role in the link between LF and GSCM of restaurants. Unique Contribution to Theory, Practice and Policy: The current study provides a novel framework by integrating institutional theory (IT) and stakeholder theory to examine how LF and customer green interests (CGI) respectively, may influence the GSCM of restaurants. With institutional theory the study suggests that restaurants` decision making depend on the external factors. It provides vital insights linking coercive pressure from the government and GSCM of restaurants. The study further challenged the stakeholder theory that customer green interest does not have any moderating role toward implementing GSCM of restaurants. Management teams of restaurants, policy makers, and other industrial stakeholders should understand that while customer green interest do not play any role in enhancing GSCM, a robust legal framework may be used as a critical factor in enhancing the GSCM of restaurants